3D measurement of movements of fish fins using high-speed cameras-II - Tan, Eugene Kia Chun (2015)
Overall, the boxfish is prestigious for its capacity to swim and move through turbulent water notwithstanding its unfavorable body shape. This highlight has drawn the consideration of analysts and is alluring for the concept of a submerged vehicle. This task means to study the relationship between the development of the fins of a boxfish and its steadiness undercurrent environment. An action camera was utilized to catch pictures of boxfish swimming in current and non-current environments. Through these processed pictures, it is evident that the fish was able to counter the moments created by the current with the movement of its fins. The discoveries from this study may give helpful concepts to the design of an autonomous underwater vehicle.